Adsorption and Diffusion Energies Calculation of Sodium Ion Battery using GeTe Anode : A Density Functional Theory Study - Putra, Septia Eka Marsha; Habibi, Fathan Akbar Nur; Simatupang, Daniel Hasiholan; Mustaqim, Amrina (Green and Sustainable Materials Society, 2024)
Sodium batteries are the most potential candidates for future and green energies storage systems. However, there are problems with structural instability in the electrodes, which affect battery performance. Therefore, this study investigated the adsorption and diffusion mechanisms at the anode using a phase puckered Germanium Telluride (GeTe) monolayer structure. Density functional theory (DFT) calculations show that the Na-adsorbed hollow Te-Te structure is the most stable adsorption configuration (-1.25 eV). In the diffusion scheme, Na atoms move through the hollow Te-Te (initial state) followed by the hollow Ge-Ge (transition state), then to the hollow Te-Te (final state). The diffusion mechanism that occurs has lowest energy of 0.09 × 10-4 eV. These results suggest that the phase puckered GeTe monolayer has the potential as a high-performance sodium battery anode.